Elit Tradisional dalam Onder Afdeling Rawas Masa Kekuasaan Belanda Tahun 1901-1942 - Agus Susilo; Sarkowi Sarkowi (LP4MK STKIP PGRI Lubuklinggau, 2019)
Traditional elites are nobles who have a very important role in society. They are highly respected in social life. These traditional elites usually have better knowledge and have better education than ordinary people. In addition, traditional elites are also very vital in land ownership. Some of the land in the Surulangun area belongs to local nobles and indigenous people as managers. Life in Surulangun was also very promising because of the life of activities around the Rawas river which became the meeting point of other traders around the Rawas river. In addition to having the Rawas river which is the lifeblood of trade in Surulangun, this area is also very strategic because it borders the Jambi area. For crops, the Surulangun area is also very large, this is the spirit of the Dutch nation along the Musi and Rawas rivers to get to Surulangun. After taking power in Surulangun, the Netherlands made this area an area of the capital of Onder Afdeling Rawas. The Dutch colonial nation held many friendships with traditional elites to support its government. In the form of Dutch cooperation with these traditional elites by promising better assets and positions, many traditional elites were interested in cooperating. On the other hand, the Netherlands wants a traditional elite as a liaison between the Netherlands and the indigenous people to manage mining and plantations in Surulangun. So that the Dutch Colonial nation became very advanced and developed rapidly after making Surulangun as one of the contributors of wealth to Dutch Colonial.